SICKLE CELL THALASSEMIA IN AN ADULT FROM CENTRAL INDIA SHOWING MASSIVE SPLENIC INFARCTION AND GAMNA-GANDY BODIES IN SPLENIC PARENCHYMA WITH CONCOMITANT PLASMODIUM FALCIPARUM INFECTION: (case report) - Singh, T. S.; Singh, R.; Pandey, R. (International Journal of Medicine and Medical Research, 2023)
Background. Sickle cell thalassemia is a heterozygous state of HbS/β+ or HbS/β0 manifested clinically either as an asymptomatic carrier or have features akin to sickle cell anemia. Objective. The aim of the study is to review the literature and discuss the varied clinical manifestations and diagnosis of a case report of haemoglobinopathy in an adult from Central India. Methods. A case of haemoglobinopathy from central part of India is being investigated. Results. A case of haemoglobinopathy in an adult presenting to a tertiary hospital with chronic back ache was reported. The patient was found to have massive splenomegaly with evidence of splenic infarction. Gross examination of spleen revealed multiple soft yellowish pasty areas, which on microscopic examination showed significant necrosis with presence of great amount pale amorphous yellow substance, Gamna-Gandy bodies (GGBs) and massive foreign body cell reaction in splenic parenchyma. Post-splenectomy peripheral blood smear (PBS) showed thrombocytosis and plasmodium falciparum gametocytes. The Hb electrophoresis revealed both elevation of Hb S (49.7%), Hb F (46.7%); Hb A2 (3.0%) and (Hb A 0.7%) consistent with as Sickle Cell Thalassemia Hb S/β+ Thalassemia. Conclusion. Sickle cell thalassemia with long standing huge splenomegaly, splenic infarction with GGBs deposition and concomitant falciparum malaria in clinically stable patient is rare indeed.